2021
DOI: 10.1037/dhe0000135
|View full text |Cite
|
Sign up to set email alerts
|

The within-group differences in LGBQ+ college students’ belongingness, institutional commitment, and outness.

Abstract: Although scholars have examined how lesbian, gay, bisexual, and queer (LGBQϩ) students perceive their collegiate environments, few quantitative studies disaggregate data to see how populations within the LGBQϩ community experience certain outcomes. The purpose of this quantitative study was to investigate how student subgroups within the LGBQϩ community differed in their perceptions of belongingness, institutional commitment, and outness. Using large-scale, multi-institution data from thousands of first-year a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 41 publications
0
10
0
3
Order By: Relevance
“…This is important to consider because research has suggested that individuals who identify as bisexual are at higher risk of assault (i.e., can impact perceptions of safety), are often ostracized from both the LGBAϩ and heterosexual communities (i.e., can impact sense of belonging), and have higher rates of mental health difficulties than other sexual minority groups (Centers for Disease Control & Prevention, 2010; Kerr et al, 2013;Yost & Thomas, 2012). Conversely, other research has suggested that college students who identify as bisexual have higher levels of belonging than other sexual orientation groups (BrckaLorenz et al, 2019). The second most frequently reported identity within our sample was asexual.…”
Section: Results In the Context Of Prior Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…This is important to consider because research has suggested that individuals who identify as bisexual are at higher risk of assault (i.e., can impact perceptions of safety), are often ostracized from both the LGBAϩ and heterosexual communities (i.e., can impact sense of belonging), and have higher rates of mental health difficulties than other sexual minority groups (Centers for Disease Control & Prevention, 2010; Kerr et al, 2013;Yost & Thomas, 2012). Conversely, other research has suggested that college students who identify as bisexual have higher levels of belonging than other sexual orientation groups (BrckaLorenz et al, 2019). The second most frequently reported identity within our sample was asexual.…”
Section: Results In the Context Of Prior Literaturementioning
confidence: 99%
“…Although follow-up research is necessary to elucidate the discrepancies in findings, it is possible that other aspects of the participants’ identities drive these differences seen across studies. More specifically, BrckaLorenz et al (2019) found that race also contributed to students’ sense of belonging on college campuses. Specifically, White LGBA+ students reported lower belonging than LGBA+ students of other races.…”
Section: Discussionmentioning
confidence: 99%
“…Extending these complications, belongingness for gay SOC was compromised by participating in a residential environment marked by connections to academic support (i.e., supportive educational environment) and by interactions with faculty to a greater degree than their lesbian, bisexual, and queer counterparts. With privilege comes expectation—expecting to find the academic support in the residence halls and expecting all interactions with faculty to yield positive results; perhaps the privileges held by these students extend into academic practice in ways similar to other privileged students (e.g., White LGBQ+ students reporting a lower sense of belonging compared with other racial groups; see BrckaLorenz et al, 2019). Surely, more research is needed to unpack these important and nuanced findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, scholars have only recently started to explore the within-group differences that may exist in the LGBQ+ SOC community. Of note, BrckaLorenz et al’s (2019) research using data from the National Survey of Student Engagement revealed that when compared with the average student, LGBQ+ Asian students reported a higher sense of belonging while LGBQ+ White students indicated lower belongingness. Though surprising, LGBQ+ White students may focus greatly on the oppressive experiences they have tied to their sexuality while obscuring the racial privilege they encounter on campus (BrckaLorenz et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, they reported how often they have had discussions with LGBQ+ people or about LGBQ+ issues outside of class. These items were created by NSSE researchers to study a variety of LGBQ+ issues including students’ sense of belonging, experiences with discrimination, interactions with LGBQ+ others, and the inclusion of LGBQ+ topics in conversations, curricular experiences, and programming (BrckaLorenz, Duran, Fassett, & Palmer, 2019; NSSE, 2017). These items directly address the second and third tiers of our framework: culturally engaging courses and supportive campus environment.…”
Section: Methodsmentioning
confidence: 99%